Bioethics in Latin America: 1989-1991 - Mainetti, José Alberto (1992)
In our region, bioethics as an academic discipline and a public movement is still in its beginning stages. The historical changes resulting from scientific and technological advances in biomedicine and from the liberal and pluralist character of industrialized countries have barely begun to occur in the developing countries of Latin America, which remain largely “pretechnical” in their orientation. Bioethics as a secular discipline, with its principles of beneficence, autonomy, and justice, and its emphasis on the rational and free agent in the therapeutic relationship, has not yet reached Latin America.